Authority of Regional Government in Fulfilling Lactation Rooms in Office Area - Subiyanto, Imam (IHSA Institute, 2024)
Breast milk is a crucial issue in the public domain and is of concern to many countries in achieving the Millennium Development Goals (MDGs) in the health sector. The government needs to support breastfeeding, one of which is by providing lactation rooms in public places, including office environments. This research aims to analyze the authority of local governments in providing lactation rooms in office environments based on Government Regulation Number 33 of 2012 concerning breastfeeding. The research method uses a normative legal approach based on Authority Theory, Rule of Law Theory and Welfare State Theory. Field findings concluded that the regional government's authority to provide lactation rooms in office environments is based on Government Regulation Number 33 of 2012 concerning breastfeeding related to basic services as regulated in Article 11 paragraph (2) of Law Number 23 of 2014 concerning Regional Government. Regional governments are expected to make regional regulations that specifically serve as a legal umbrella for providing lactation rooms because in general the government is responsible for establishing policies in the form of creating norms, standards, procedures and criteria to fulfill the provision of lactation rooms, especially in office environments